Arthur Conan Doyle and photography : traces, fairies and other apparitions - Stiegler, Bernd (Edinburgh University Press, 2023)
Arthur Conan Doyle is best known as the author of the Sherlock Holmes stories. However, his works are far more extensive than these familiar works. They include historical novels, political pamphlets, historical studies, science fiction novels and, last but not least, numerous publications on spiritualism. Photography plays a central role in his work and gives rise to a highly peculiar world of imagination. The photographs allow us to take a look at the world in around 1900 with all its oddities. For Conan Doyle's contemporaries, Sherlock Holmes was a real figure. To Conan Doyle, photographs of elves, the dead and ghosts testified to their existence. This book collects these images, along with the imaginarium that surrounds them.
Translated from the German.
Keywords: Doyle, Arthur Conan, -- 1859-1930; Spiritualism -- Great Britain -- History.; Literature and photography -- Great Britain -- History.; Spiritisme -- Grande-Bretagne -- Histoire.; Littérature et photographie -- Grande-Bretagne -- Histoire.; Literature and photography; Spiritualism; Great Britain; Literature: history & criticism.; Literary studies: fiction, novelists & prose writers.; Spirituality & religious experience.; Literature.; Electronic books.; History